1997
DOI: 10.2476/asjaa.46.115
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Amino Acid Sequence Comparison of Hemocyanin Subunits from the Spiders, Argiope amoena, Argiope bruennichii, Araneus ventricosus, Nephila clavata and Dolomedes sulfureus.

Abstract: By two dimensional electrophoresis using acrylamide disc and slab gels, hemocyanin hexamers of four araneid spiders Argiope amoena, A. bruennichii, Araneus ventricosus, Nephila clavata, and a pisaurid spider Dolomedes sulfureus were separated completely into individual subunits. Direct protein sequencing of hemocyanin monomer subunits gave the N-terminal sequences for the first 10-25 amino acid residues, except for subunits with blocked amino terminals. From the sequence comparison between the araneid spider's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…1 and analyzed the N-terminals of these monomer subunits. The Nterminal amino acid sequences of twenty-two monomer subunits were determined, because the subunits AR1-3, AY1-3 and AK1 could not be sequenced for the N-terminals, suggesting blocked amino terminals, which were reported in hemocyanin subunits of a scorpion (Ali et al, 1995) and araneomorph spiders (Takasu and Sugita, 1997). Direct protein sequencing of the hemocyanin monomers presented the sequences for the first 13 -43 amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and analyzed the N-terminals of these monomer subunits. The Nterminal amino acid sequences of twenty-two monomer subunits were determined, because the subunits AR1-3, AY1-3 and AK1 could not be sequenced for the N-terminals, suggesting blocked amino terminals, which were reported in hemocyanin subunits of a scorpion (Ali et al, 1995) and araneomorph spiders (Takasu and Sugita, 1997). Direct protein sequencing of the hemocyanin monomers presented the sequences for the first 13 -43 amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…The hemocyanin subunits in a disc gel were re-electrophoresed into a slab gel to separate hemocyanin subunits completely (Takasu and Sugita, 1997) and the subunits in the slab gel were transferred to a polyvinylidene difluoride (PVDF) membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomer subunits associate noncovalently in most cases, although a few hemocyanins contain one or more disulfide-linked dimers (Van Holde and Miller, 1995). The heterogeneity of the monomer subunits of spider and scorpion hemocyanins has been demonstrated by means of polyacrylamide gel electrophoresis (Sugita and Sekiguchi, 1975;Takasu and Sugita, 1997;Sugita et al, 1999;Kuwada and Sugita, 2000), but each of these subunits has a mass of about 75KDa and carries one oxygen-binding site, suggesting that all are clearly derived from a common ancestral protein (Van Holde and Miller, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As the first step to make species tree of spiders using the hemocyanin subunit sequence data, Takasu and Sugita (1997) analyzed the N-terminal amino acid sequences of hemocyanin monomer subunits from four araneid spiders and reported that duplications of monomer subunit occurred in the lineages of Argiope amoena and Nephila clavata or in the common ancestor immediately before the divergence of these two spiders and then in the lineage of N clavata. Thus, they could show that N-terminal amino acid analysis is available not only to find orthologous subunits but also to study the molecular evolution of hemocyanin subunits.…”
Section: Introductionmentioning
confidence: 99%